2012
DOI: 10.1007/s10853-012-6381-7
|View full text |Cite
|
Sign up to set email alerts
|

Electro co-deposition of Ni–Al2O3 composite coatings

Abstract: Nickel-Al 2 O 3 composite coatings have been successfully deposited galvanostatically on to stainless steel substrates by electro co-deposition from a Watts bath containing between 50 and 150 g/l of sub-micron or nanosized alumina particles applying current density of -10, -20 and -32 mA cm -2 . The alumina distribution in the composite films on the two sides of the substrate was remarkably different due to solution hydrodynamics and electric field effects. The effect of current density, particle concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 71 publications
(193 reference statements)
2
16
0
Order By: Relevance
“…Details of the electrochemical conditions for electroplating nickel on stainless steel from a nickel sulphate bath are available in Corni 1, 20. The alumina particles used for the composite ranged from one micron to the nanoscale in an electroplated layer that was typically between ten and twenty microns thick with alumina particle concentrations between 10 and 25 vol%.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the electrochemical conditions for electroplating nickel on stainless steel from a nickel sulphate bath are available in Corni 1, 20. The alumina particles used for the composite ranged from one micron to the nanoscale in an electroplated layer that was typically between ten and twenty microns thick with alumina particle concentrations between 10 and 25 vol%.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, prior studies have shown that Ni-W coatings exhibited a clearly increased corrosion resistance compared to pure Ni coating. Recently, in the field of galvanic deposition, various Ni-W-based composite films containing micro-and nano-sized inorganic inert particles that have been developed through the electrodepositing technique involving Ni-W-Al 2 O 3 [7][8], Ni-W-TiO 2 [9], Ni-W-diamond [10], Ni-W-SiC [11], Ni-W-WC [12], Ni-W-CeO 2 [13], Ni-W-Co [14], Ni-W-B [15], and Ni-carbon nanotubes (CNTs) alloys [16][17][18]. Yang et al [5] reported that application of heat treatment at 400°C for 1 h increased the corrosion current density (i corr ) and the corrosion potential (E corr ) of Ni-W alloys in 3.5 wt-% NaCl solution, due to grain boundary relaxation upon heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on other investigations, the addition of particles can change the diffusion‐controlled process to a charge‐controlled process, and the decreasing charge transfer leads to the higher nucleation rate of Ni. According to the research communities, the incorporation of particles either occurs because of the particle adsorption on the surface or because of the reduction of the metal ions adsorbed on the particle surface . Some researchers also believe that alumina has no effect on the reduction, whereas others claim that this effect can only be visible in concentrations higher than 40 g/l.…”
Section: Resultsmentioning
confidence: 99%